Embedding hydrophobic MoS2 nanosheets within hydrophilic sodium alginate membrane for enhanced ethanol dehydration. (10th August 2018) - Song, Yimeng; Jiang, Zhongyi; Gao, Boxin; Wang, Hongjian; Wang, Meidi; He, Ze; Cao, Xinyue; Pan, Fusheng
Graphical abstract: Highlights: MoS2 nanosheets are embedded within polymer matrix to prepare hybrid membrane. The hydrophobic surface of MoS2 facilitates the transport of water molecules. Hybrid membrane exhibits low swelling degree and excellent mechanical property. Hybrid membrane exhibits good separation performance for ethanol dehydration. Abstract: Molybdenum disulfide (MoS2 ), as an emerging kind of two-dimensional (2D) materials with large hydrophobic surface and superior mechanical property, holds great promise in preparing high-performance hybrid membranes. In this study, MoS2 nanosheets were embedded within sodium alginate (SA) for ethanol/water separation. Morphology, structure, mechanical and thermal properties of the membranes were characterized. The incorporation of MoS2 nanosheets affected the microstructure of the membranes. The Young's modulus of the as-fabricated hybrid membrane was enhanced by 57%, and the swelling degree was reduced by 33% compared to SA pure membrane. Besides, the ordered stacking of MoS2 nanosheets, as well as their interlayer spacings, provided transport channels for water molecules. The fast transport of water molecules on the MoS2 surface is the reason that an optimum ethanol dehydration performance was achieved when the MoS2 content was 2 wt%. In ethanol/water (90/10 wt%) solution at 350 K, the permeation flux was 1839 g/(m 2  h) (54% higher than that of SA/PAN pure membrane), and the separation factor was 1229 (85% greater than that of SA/PAN pure membrane). Moreover, the hybrid membrane exhibited good long-term operation stability.